Lanthanides/Actinides: Physics I - Gschneidner, Karl A. (Handbook on the physics and chemistry of rare earths ;, 1993)
This volume of the Handbook is the first of a three volume set of reviews devoted to the interrelationships, similarities, differences and contrasts of the lanthanide and actinide series of elements. In order to comprehensively cover this large field two leading scientists, G.H. Lander and G.R. Choppin, were invited to be guest editors for this special set of volumes. Together, the four editors carefully and critically chose the various topics and invited the appropriate experts to write reviews keeping in mind that the emphasis was to be on the interrelationships of the lanthanides and actinides. The volume contains eight chapters concerned with some of the physical aspects of the lanthanide and actinide series. The first three chapters are theoretical in nature and the last five are more heavily oriented towards experimental studies.